Transformasi Estetika: Pencak Silat Bandrong Menjadi Tari Bandrong Ing Cilegon - Azkia Ismiati; Malarsih Malarsih; Deasylina Da Ary (Ideas Publishing, 2023)
Bandrong ing Cilegon dance is a cultural heritage of Cilegon City which was created in 2012. Bandrong ing Cilegon dance was born from the transformation process of the bandrong pencak silat martial arts into bandrong ing Cilegon dance which is based on the changing factors. The main objective in this research is to find out the factors of change that bridge the process of transforming the movements of the Bandrong Pencak Silat martial arts into aesthetic movements in the Bandrong Ing Cilegon dance. The research method used is the imitative approach, ethnochoreology, and art education. The results this study that there are three core moves in pencak silat bandrong are then transformed into fifteen movements of the bandrong ing Cilegon dance. While factors that bridge the transformation process based on customs, society, and government, as well as inherent character values in the bandrong ing Cilegon dance, namely patriotic values.